Production And Partial Purification Of Leucine Aminopeptidase From Aeromonas Proteolytica (ATCC 15338) - PUSPADHWAJA MALL; VARUN KUMAR; VIRAT PARIKH; DEVANSH DAVE; BINITA TUNGA; RASHBEHARI TUNGA (International Journal of Pharma and Bio Sciences, 2011)
Aeromonas proteolytica (ATCC 15338) was grown at flask level and fermenter level in different concentrations of LB. LB at 4 % was found to be optimum for maximum production of Aminopeptidase. At flask level, 30 °C and 180 rpm was found to be optimum. In fermenter level, Aminopeptidase was successfully produced at 30 °C, 700 rpm, pH 7.0 ± 0.05 and airflow of 0.5 LPM. Partial purification of the protein was achieved by ion exchange chromatography on DEAE sepharose. Aminopeptidase was eluted between 170 mM and 230 mM of NaCl concentration in a gradient elution process. Buffer exchange was done by gel filtration chromatography (Sephadex G25). In reverse phase high performance liquid chromatography (RP-HPLC), the retention time of standard and that of the partially purified Aminopeptidase was recorded at ~12 min. Molecular weight and iso electric point of standard (Aminopeptidase from Sigma) and partially purified Aminopeptidase were found to be ~30 kD and 3.5 respectively.